Induction of the Stringent Response Underlies the Antimicrobial Action of Aliphatic Isothiocyanates - Nowicki, Dariusz; Krause, Klaudyna; Szamborska, Patrycja; Żukowska, Adrianna; Cech, Grzegorz M.; Szalewska-Pałasz, Agnieszka (Frontiers in Microbiology, 2021)
The bacterial resistance to known antibiotics comprises a serious threat to public health. The propagation of multidrug-resistant pathogenic strains is a reason for undertaking a search for new therapeutic strategies, based on newly developed chemical compounds and the agents present in nature. Moreover, the antibiotic treatment of the infections by enterotoxin toxin bearing strain - enterohaemorrhagic Escherichia coli (EHEC) is considered hazardous and controversial due to the possibility to induction of bacteriophage-encoded toxin production by the antibiotic-mediated stress. The important source of potentially beneficial compounds are secondary plant metabolites, isothiocyanates (ITC), phytoncides from Brassicaceae family. We reported previously that sulforaphane and phenethyl isothiocyanate, known already for their chemopreventive and anticancer features, exhibit significant antibacterial effects against various pathogenic bacteria. The mechanisms of their action is based on the induction of the stringent response and accumulation of its alarmons, guanosine penta- and tetraphosphate. In this process, the amino acid starvation path is employed via RelA protein, however, the precise mechanism of amino acid limitation in the presence of ITC is yet unknown. In this work, we asked whether ITC could act synergistically with each other to increase the antibacterial effect. The set of aliphatic ITC such as iberin, iberverin, alyssin, erucin, sulforaphen, erysolin, cheirolin was tested in the combination of sulforaphane against E. coli. Our experiments showed that all tested ITC exhibit strong antimicrobial effect individually, and this effect involves the stringent response caused by the amino acid starvation. Interestingly, excess of specific amino acids reversed the antimicrobial effects of ITC, where the common amino acid for all tested compounds was glycine. The synergic action observed for iberin, iberverin, alyssin also led to the accumulation of (p)ppGpp, and the minimal inhibitory concentration necessary for the antibacterial effect was 4-8 fold lower than for individual ITC. Moreover, the unique mode of ITC action is responsible for the inhibition of prophage induction and the toxin production in addition to growth inhibition of EHEC strains. Thus, the antimicrobial effect of plant secondary metabolites by the stringent response induction could be employed in potential therapeutic strategies.